2012
DOI: 10.1002/hup.2217
|View full text |Cite
|
Sign up to set email alerts
|

Clinically relevant drug interactions in anxiety disorders

Abstract: The potential for drug interactions with medications used in anxiety disorders should be the cause of clinical concern, particularly in elderly individuals. However, the liability for harmful drug interactions may be anticipated, and the risk reduced. Although not all interactions are clinically relevant, careful monitoring of clinical response and possible interactions is essential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 134 publications
(151 reference statements)
0
22
0
1
Order By: Relevance
“…Prescribers frequently substitute one SSRI for another if the first is ineffective or poorly tolerated, and non-pharmacokinetic/pharmacologic factors often drive prescribing habits. If the use of potentially interacting drugs cannot be avoided, adverse clinical consequences may be minimized with individualized dose adjustments guided by clinical response or monitoring plasma drug concentrations, but that approach is used minimally in practice [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Prescribers frequently substitute one SSRI for another if the first is ineffective or poorly tolerated, and non-pharmacokinetic/pharmacologic factors often drive prescribing habits. If the use of potentially interacting drugs cannot be avoided, adverse clinical consequences may be minimized with individualized dose adjustments guided by clinical response or monitoring plasma drug concentrations, but that approach is used minimally in practice [24]. …”
Section: Discussionmentioning
confidence: 99%
“…Pooling several clinical trials, it was found that quetiapine was better than placebo in both the maintenance and treatment of GAD [64]. Although not as strong as for monotherapy, there are also some studies that support quetiapine as an adjunctive therapy [65].…”
Section: Antipsychoticsmentioning
confidence: 99%
“…In particular, an Agency for Health Care, Research and Quality (AHRQ) review found that they may be beneficial in both obsessive-compulsive disorder (OCD) and post-traumatic stress disorder (PTSD). It found that studies of both risperidone and quetiapine have shown significant effects when used as augmentation to treatment with SSRIs [64]. In head to head studies of augmentation treatment, there was no significant difference between olanzapine and risperidone with an SSRI, while quetiapine has been shown to have better efficacy than ziprasidone as an adjuvant [64].…”
Section: Antipsychoticsmentioning
confidence: 99%
“…FVX is extensively metabolized to 11 metabolites, but all of them are devoid of any significant pharmacological activity [8,9] . Most importantly, this antidepressant has a potent inhibitory effect on the activity of CYP1A2 and CYP2C19, while it is also considered a moderate inhibitor of CYP2C9 and CYP3A4 and a weak inhibitor of CYP2D6 [10,11] . Taking into account that CYP2D6 is the same metabolic pathway involved in the biotransformation of ATX, the aim of the present study was to investigate whether FVX influences its pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%